Parametric Study of One-Dimensional Seismic Site Response Analyses Based on Local Soil Condition of Jakarta - Misliniyati, Rena; Sahadewa, Andhika; Hendriyawan, Hendriyawan; Irsyam, Masyhur (ITB Journal Publisher, LPPM ITB, 2019)
Seismic site response analysis is used to estimate the response of soil deposits during seismic loading at any depth of interest and to interpret time histories as well as response spectra. This type of analysis involves many parameters that can affect the character of ground shaking. It is important to know the effect of these parameters in order to perform reliable seismic hazard evaluation at a site. This paper presents the effects of several parameters toward the characteristics of surface response spectra based on the local soil conditions of Jakarta using a one-dimensional (1-D) site response model with total stress approach. A parametric study was performed on two cohesive soil deposit profiles with a different site class, namely medium clay (site SD) and soft clay (site SE). The bedrock layers of both profiles were located at a depth of 300 m. In this study, the analytical methods implemented were the equivalent-linear method and the non-linear method. Several different dynamics soil models were also implemented. In addition, variation of property parameters, such as depth of bedrock, shear wave velocity of bedrock, layer thickness, etc., were studied. The results of this study indicate that all of the studied parameters have a significant effect on the response spectra at the ground surface.